EFEKTIFITAS PENERAPAN PEMBATASAN USIA NIKAH UU NOMOR 16 TAHUN 2019 PASAL 7 TENTANG PERNIKAHAN ANAK STUDI KASUS KUA KECAMATAN BELAWA KABUPATEN WAJO: indonesia - Nurhasmi; Jamil, Muh. Jamal; Amir, Rahma (Universitas Islam Negeri Alauddin Makassar, 2023)
This thesis discusses the effectiveness of the application of the age limit for marriage in Article 7 of Law Number 16 of 2019 on child marriage. From the main problem, the writer formulates several sub-problems, namely: 1. What is the nature of the age limit for marriage according to Article 7 of Law Number 16 of 2019 concerning Child Marriage? 2. How is the application of the age limit for marriage in Article 7 of Law Number 16 of 2019 concerning child marriage at the KUA, Belawa District, Wajo Regency? This type of research is research (field research) is a form of field research or it can also be called qualitative research, field research is carried out using the method of observation, interviews, and describes the facts that occur in the field with the legal research approach used, namely the Law approach. laws and case approaches, because what is being researched is how the implementation of Law Number 16 of 2019 at the KUA in Belawa District is. The results of this study indicate that 1. The age limit for marriage is raised to 19 years for both women and men because 19 years of age is considered mature in terms of emotional, biological and psychological aspects. 2. The marriage age limit permitted by the Belawa District Government is 19 years which is expected to reduce the number of child marriages, although it is not significant, but the reform of the law can be said to be quite effective in tackling the number of child marriages. The implication of this research is, when they want to get married, it is better if the parents of the bride and groom or the person who should do the marriage pay more attention to the age limit for marriage so that the purpose of marriage can be achieved and village priests and community leaders should take part in helping to increase public awareness in counseling. religion and cooperate with the local Office of Religious Affairs (KUA), particularly regarding marriage issues.